Effect of Bacillus firmus on antibody formation after mucosal and parenteral immunization in mice - Prokesová, L; Mlcková, P; Stanková, I; Chloubová, A; Novotná, V; Ladmanová, P; Chalupná, P; Mára, M (Immunology letters, 1998)
Immunostimulatory properties of B. firmus, a nontoxic, nonpathogenic G + bacterium of external environment, were described previously. Antiinfectious and antitumor activity, macrophage activation and strong polyclonal stimulation of B lymphocytes were proved in human, mice and rats. The adjuvant effect of B. firmus on specific antibody response to ovalbumin in BALB/c mice is the topic of the present study. Against our expectation, B. firmus exerts more suppressive than stimulatory effect on specific antibody response. Formolized B. firmus decreased anti-ovalbumin response after subcutaneous immunization and only slightly increased serum antibodies after intraperitoneal immunization. After mucosal immunization, both oral and rectal, ovalbumin itself did not cause a significant systemic response but induced IgA anti-ovalbumin response in the intestine. B. firmus applied together with ovalbumin increased systemic serum response but absolutely eliminated intestinal response. The rectal route of antigen administration has been found less convenient because of less precise dosing of antigen in this mode of immunization.
Keywords: protilátky bakteriální; Animals; injekce intraperitoneální; Female; Ovalbumin; antigeny bakteriální; ženské pohlaví; Administration, Rectal; Adjuvants, Immunologic; Antibody Formation; Injections, Intraperitoneal; Intestine, Small; Mice; tvorba protilátek; injekce subkutánní; myši; Immunoglobulins; Antibodies, Bacterial; imunizace; Immunization; aplikace rektální; aplikace orální; Injections, Subcutaneous; Antigens, Bacterial; Bacillus; Administration, Oral; zvířata; imunoglobuliny; adjuvancia imunologická; ovalbumin; tenké střevo